Changes in foot pressure distribution during a combined running and cycling test - Hottenrott, K.; Hoos, O.; Sommer, H. M. (1998)
Introduction: Very often the great training demands in running lead to an overload of the musculo-skeletal system. Alternative training methods like cycling would be very useful to reduce this overload. In this connection the question arises of how these triathlon-specific combined exercises affect running economy and foot pressure distribution (FPD). Methods: 24 national and international elite triathletes (7 female, V02max 64,3 ml kg-1 min-1, 17 male, V02max 71,2 ml kg-1 min-1) performed a combined runningcycling test in the laboratory. The combined test design consists of three running step tests with two different speed levels (R1, R3, R4). Between R1 and R3 a 20 min endurance exercise test in running, and between R3 and R4 a 30 min endurance exercise test in cycling were each performed with an intensity of 80% V02max. Foot pressure distribution (Novel, Pedar-System), surface electromyography (Biovision), lactate and heart rate were measured in running and cycling. For determination of the pedar masks, the soles of the feet were divided into 9 anatomical masks (Bontranger et al., 1997). Results: The results showed that there were no significant changes in contact area, maximum vertical forces, vertical displacement, contact time between R1 and R3. In contrast to that, after the cycling exercise significant increases were shown between R1 and R4 in maximum vertical forces (v1: +15%, v2: +12 %) and vertical displacement (v1: +9%). Primarily, the changes result from the middle part of the metatarsus. Conclusion: Athletes should be careful when practicing running immediately after cycling in order to reduce vertical stresses. References: Bontranger, E.L., Boyd, L.A. et al. (1997). Determination of Novel Pedar Masks using Harris Mat Imprints. Gait & Posture 4, 167-168.